A Hybrid Algorithm for Multi-Beam Steering of LCOS-Based Wavelength Selective Switch - Yunshu Gao; Zhongwei Tan; Xiao Chen; Genxiang Chen (IEEE Photonics Journal, 2020)
Iterative Fourier transform algorithm (IFTA) has been widely applied to achieve holograms in diffractive optical elements, however it is insufficient for designing holograms uploaded on liquid crystal on silicon (LCOS) to steer multi-beams in a wavelength selective switch (WSS). In this paper, a three-step hybrid algorithm including IFTA, Symmetrical IFTA with both phase and amplitude freedoms (SIFTA-2) and Genetic algorithm (GA) is developed to optimize the multi-casting hologram and experimentally demonstrated the multi-casting function of WSS. The reconstructed output field not only has max 128 fan-out patterns with flexible power ratio, but also can be adjusted to balance multi-indicators like reconstructed root mean square error (RMSE), diffraction efficiency and crosstalk power by setting flexible weightings of fitness functions in GA.